MR-plastination-arthrography: a new technique used to study the distal tibiofibular syndesmosis - Hermans, John J. (Skeletal Radiol, 2009)
PURPOSE: The purpose of this study was to describe a new technique called MR plastination arthrography to study both intra- and extra-articular anatomy. MATERIALS AND METHODS: In six human cadaveric lower legs MR arthrography was performed in either a one-step or two-step procedure. In the former a mixture of diluted Gadolinium and dyed polymer was injected. In the latter the dyed polymer was injected after arthrography wih diluted Gadolinium. Three-millimeter slices of these legs, obtained in a plane identical to that of the MR images, were plastinated according to the E12 technique of von Hagens. The plastination slices were subsequently compared with the MR images. RESULTS: The one-step procedure resulted in an inhomogeneous arthrogram. The two-step procedure resulted in a good correlation between the high-resolution MR images and plastination slices, as expressed by a good comparison of anatomic detail of the small syndesmotic recess. CONCLUSIONS: Images of the distal tibiofibular syndesmosis obtained with plastination arthrography correlated well with images acquired by MR arthrography when performed in a two-step procedure.